2016
DOI: 10.3897/subtbiol.20.9334
|View full text |Cite
|
Sign up to set email alerts
|

Are inner cave communities more stable than entrance communities in Lapa Nova show cave?

Abstract: Citation: Pellegrini TG, Ferreira RL (2016) Are inner cave communities more stable than entrance communities in Lapa Nova show cave? Subterranean Biology 20: 15-37. Abstract Lapa Nova is a dolomitic Brazilian show cave. Invertebrate fauna registered for this cave is quite rich and abundant. During two intensive surveys in 2009, 24,482 invertebrate individuals belonging to 187 species were sampled. We found 160 species in April sampling, while in September sampling richness was considerably lower, 102 species, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
1
6
0
1
Order By: Relevance
“…Our study showed a general constancy in both composition and distribution along the cave of the entire faunal community, at least during the seven-year period investigated. Therefore, the starting hypothesis of a low inter-annual variability characterizing subterranean biological communities [2,14,16] was corroborated by our multivariate approach. Consequently, our results seem to extend the hypothesis of low temporal variability of subterranean ecosystems to recently-established biological communities colonizing human-made habitats, in particular those characterized by highly buffered climatic conditions.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Our study showed a general constancy in both composition and distribution along the cave of the entire faunal community, at least during the seven-year period investigated. Therefore, the starting hypothesis of a low inter-annual variability characterizing subterranean biological communities [2,14,16] was corroborated by our multivariate approach. Consequently, our results seem to extend the hypothesis of low temporal variability of subterranean ecosystems to recently-established biological communities colonizing human-made habitats, in particular those characterized by highly buffered climatic conditions.…”
Section: Discussionsupporting
confidence: 68%
“…Therefore, the organic basis of the food chain in subterranean ecosystems is provided by active movements of animals that periodically migrate inside the system during external unfavorable periods or is imported as organic debris by gravity, wind, and rainflow from outside [7,8]. Several studies analyzed the influence of seasonal climatic variations on the abundance and distribution of single or few subterranean populations or species (e.g., references [4,[9][10][11][12] or, more in general, on the composition of entire biological communities living in subterranean environments e.g., references [5,[13][14][15]. Concerning the long-term composition of biological cave communities, it is generally assumed that those living in subterranean habitats are characterized by low levels of temporal variability [1,16].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the community in the vicinity of the surface is usually dominated by trogloxenes and troglophiles, whereas troglobionts became progressively more abundant at greater depths (Culver & Poulson, ; Howarth, ; Poulson & White, ; Racoviţă, ; Schiner, ; Tobin et al, ). However, recent studies showed that distributions of taxa in subterranean habitats do not always fit this general pattern (e.g., Novak et al, ; Pellegrini & Ferreira, ). Surface organisms are typically observed even at great depths in caves; for example, surface dipterans have been observed at –2,140 m in the Krubera‐Voronja Cave, Western Caucasus (Sendra & Reboleira, ).…”
Section: Introductionmentioning
confidence: 99%
“…These include, among others, small emerging drainages (hypotelminorheic habitats), cracks in the karstified rock (epikarst), lava tubes, deep soil and litter strata, air-filled space in taluses and dry riverbeds (Milieu Souterrain Superficiel; MSS) (Culver and Pipan, 2014). In a typical subterranean habitat, such as a cave, it is generally observed that the abundance and diversity of organisms progressively decrease, going from the highly populated and energy-rich twilight zone area to the energy-deprived and poorly populated deeper parts (but see Novak et al 2012 andPellegrini andFerreira 2016 for counterexamples). All the air-and water-filled subterranean spaces representing habitats for subterranean species.…”
Section: Stable Environmental Conditionsmentioning
confidence: 99%
“…A classical schematic representation of a cave. In a typical subterranean habitat, such as a cave, it is generally observed that the abundance and diversity of organisms progressively decrease, going from the highly populated and energy-rich twilight zone area to the energy-deprived and poorly populated deeper parts (but see Novak et al 2012 andPellegrini andFerreira 2016 for counterexamples). The existence of gradients in the abiotic and biotic conditions from the surface toward the deepest subterranean sectors, enhance the possibility to use caves as models for ecological studies, e.g.…”
Section: Stable Environmental Conditionsmentioning
confidence: 99%